Diagnosis of pulmonary tuberculosis from gastric aspirate samples in nonexpectorating pediatric patients in a tertiary care hospital - Shiwangi Sharma; Anuradha Shulania; Arvind Achra; Hishmi Jeram; Stuti Kansra; Nandini Duggal (Wolters Kluwer Medknow Publications, 2020)
Objectives: The aim of this study was to assess the utility of Xpert assay, Ziehl-Neelsen (ZN) staining, and Mycobacteria Growth Indicator Tube (MGIT™) culture for diagnosis of pediatric pulmonary tuberculosis from gastric aspirate (GA) samples and to compare Xpert assay and ZN staining with MGIT rapid liquid culture. Materials and Methods: GA samples from 210 nonexpectorating children, aged between 6 months to 12 years, presenting to the pediatric out-patient department (OPD) with clinical suspicion of tuberculosis (TB) were collected. The samples were tested by GeneXpert, ZN staining, and MGIT liquid culture. Results: GeneXpert is a more sensitive method for rapid and early diagnosis of pediatric TB when compared with microscopy.